The ethical pathway of individuals with stroke-A follow-up study - Rannikko Sunna; Suhonen Riitta; Pasanen Miko; Leino-Kilpi Helena (Blackwell Science, 2025)
Aim
To analyse the ethical pathway as perceived by individuals with stroke (IwS) in the first three post-stroke months. In the novel concept of ethical pathway, dignity, privacy, and autonomy are considered as dimensions of the ethical pathway while the pathway illustrates their potential change in the post-stroke time. Furthermore, the focus of interest was on whether the perceived realisation of values is associated with the life situational factors of symptoms diminishing functioning, social environment, and self-empowerment.
Methodological Design and Justification
A follow-up study with a descriptive correlational design was used to capture the changes in the perceived realisation of values.
Ethical Issues and Approval
The study followed the ethical principles of research involving human participants. The study was approved by the ethics committee of the university and one of the university hospitals following national standards. Permission to conduct the study was obtained from the university hospitals.
Research Methods and Instrument
Data were collected from IwS after the onset of stroke and 3\u2009months post-stroke with the Ethical Pathway of Individuals with Stroke instrument and background questions and were analysed statistically.
Results
Thirty-six participants completed the questionnaire at both measurement points. Wide variety in the ethical pathway was detected. IwS' perceived dignity decreased and autonomy increased. Privacy did not change significantly. Of the life situational factors, IwS perceived less symptoms diminishing functioning and stronger self-empowerment while social environment was perceived as rather stable. Only one association was detected between the dimensions of the ethical pathway and life situational factors: autonomy had a low negative correlation with social environment of health care professionals.
Conclusions and Study Limitations
The results provide preliminary evidence of the dynamic nature of the ethical pathway. The ethical pathway was incompletely realised for most participants and requires special attention and improvement in health care. The sample size is small and the results are therefore not generalisable.